Development of Booklet-Based Teaching Materials to Improve Mufrodat Mastery of Students at MIN 3 Nagan Raya - Ardiman Fadhil (Journal of Indonesian Primary School, 2025)
Vocabulary (mufrodat) mastery is an essential component in Arabic language learning at the madrasah ibtidaiyah level. However, classroom observations indicate that students’ vocabulary mastery remains low due to the limited availability of attractive and student-centered teaching materials. This study aims to develop booklet-based teaching materials that are valid, practical, and effective in improving the vocabulary mastery of fifth-grade students at MIN 3 Nagan Raya. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were fifth-grade students of MIN 3 Nagan Raya. Data were collected through observation, interviews, questionnaires, and pretest–posttest assessments. The results of expert validation showed that the material validity reached 91.25% and media validity reached 93.75%, both categorized as very valid. The field trial results indicated positive responses from teachers and students, with an average score of 83.5% categorized as very good. Furthermore, the students’ average vocabulary mastery score increased from 62.4 in the pretest to 82.6 in the posttest. These findings indicate that the developed booklet-based teaching materials are valid, practical, and effective in improving students’ Arabic vocabulary mastery.